2007
DOI: 10.1002/imhj.20156
|View full text |Cite
|
Sign up to set email alerts
|

Measures of effortful regulation for young children

Abstract: Emotion-related regulation is a topic of increasing interest among researchers, yet there is little agreement on ways to measure emotion regulation in young children. In this paper, we first consider important conceptual distinctions in regard to the different types of emotion-related regulation and control. Next, we describe a number of ways researchers have assessed children's regulation. We also present data from the Toddler Emotional Development project, in which laboratory-based measures of effortful regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 63 publications
(80 reference statements)
3
45
0
2
Order By: Relevance
“…Within the non-eating self-regulation measures, the relationships we found between executive functioning, effortful control, and delay of gratification were typical of what has been found in previous studies—i.e., low to moderate positive correlations between measures (Bull & Scerif, 2001; Lehto et al, 2003; Spinrad et al, 2007; Wiebe et al, 2008). Of the three measures of non-eating self-regulation used in this study, only the gift delay task did not show associations with the other measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the non-eating self-regulation measures, the relationships we found between executive functioning, effortful control, and delay of gratification were typical of what has been found in previous studies—i.e., low to moderate positive correlations between measures (Bull & Scerif, 2001; Lehto et al, 2003; Spinrad et al, 2007; Wiebe et al, 2008). Of the three measures of non-eating self-regulation used in this study, only the gift delay task did not show associations with the other measures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research shows that for the non-eating domain, within-domain correlations are usually small to moderate with correlations between measures of executive functioning generally ranging between r = 0.20 and r = 0.35 (Bull & Scerif, 2001; Lehto, Juujarvi, Kooistra, & Pulkkinen, 2003; Wiebe, Espy, & Charak, 2008). Executive functioning and effortful control show similar correlations with measures of emotion regulation (see Spinrad, Eisenberg, & Gaertner, 2007 for a review). Within the eating domain, mothers’ responses on the satiety responsiveness and food responsiveness subscales of the Children’s Eating Behavior Questionnaire (CEBQ) are negatively correlated with one another (e.g., Frankel et al, 2014; Sleddens et al, 2008; Wardle et al, 2001).…”
Section: Introductionmentioning
confidence: 91%
“…Conversely, other investigations suggest that Snack Delay is developmentally appropriate for IC assessment in 3-4 year olds (Bassett et al, 2012; Wiebe et al, 2011). Although used in the current study at 2 and 3 years of age, Dinky Toys was originally designed for preschool age children (Kochanska et al, 1996) and has been found to be difficult for children aged 30 months (Spinrad et al, 2007). Therefore, it could be that Snack Delay may be approaching a ceiling effect in 3-year-olds while Dinky Toys is more appropriate for the 3-year-olds (vs. 2-year-olds).…”
Section: Discussionmentioning
confidence: 99%
“…This ability can be operationally defined as the capacity to accomplish goal directed behavior in the face of salient, competing inputs and actions (Casey et al, 2005). A prominent component of self-control is the ability to suppress inappropriate behaviors in favor of appropriate ones, often termed impulse control (Casey et al, 1997; Rothbart et al, 2001; Spinrad et al, 2007), and can be measured by a number of self-report assessments and behavioral tasks (Mobbs et al, 2008; Somerville et al, 2011; Grose-Fifer et al, 2013). The classic go/no-go task measures the ability to maintain behavioral control in the face of interfering stimuli, by measuring an individual’s speed and accuracy when instructed to respond to a frequent target (go trial) and withhold response to a rare nontarget (no-go trial).…”
Section: Introductionmentioning
confidence: 99%